PENGUATAN WAWASAN KEBANGSAAN UNTUK MENCEGAH PAHAM RADIKALISME DAN INTOLERANSI DI KALANGAN PELAJAR SMK YAPIKA MAKASSAR - Aminuddin, Andi Muh. Adam; Imanuddin, Imanuddin; Rifaldy, Mochamad; Aotari, Wanti; Pariati, Pariati; Zulkarnain, Zulkarnain (Jurnal Ilmiah Amanah Akademika, 2022)
In this digital age and the rapid development of media, there are many things that cannot be stopped. One of them is the emergence of various negative sides which worsen the image of teenagers, especially high school/vocational school students. The influence of the digital world and developments over time will certainly influence teenagers' thinking. The influence of the lack of national insight on teenagers is something that brings them closer to intolerant and radical attitudes. One of the first things that arises is the truest feeling towards oneself or a group. Teenagers or students are very vulnerable to involvement with radical and intolerant ideas. Teenagers are often used as the main targets by radical groups in spreading radical ideas because teenagers are very easy to incite. The aim of this researcher is to create students who love peace and act in accordance with the philosophy of harmonious national life. The results of this research activity are that from the six vocational schools that were visited, 150 vocational school students were able to understand the importance of national insight in preventing radicalism and avoiding intolerant attitudes in friends and society. Thus, this mentoring and strengthening national insight activity was categorized as successful. Furthermore, it is hoped that there will be an increase in the quality of similar activities using other methods for students.